Pregnancy outcome in homozygous sickle cell disease: observations from the Jamaican Birth Cohort. (6th April 2021) - Lewis, G; Thame, M; Howitt, C; Hambleton, I; Serjeant, GR
Abstract : Objective: To document pregnancy outcome in homozygous sickle cell (SS) disease and in age‐matched controls with a normal haemoglobin genotype followed from birth for up to 45 years. Methods: A total of 100 000 consecutive non‐operative deliveries screened for sickle cell disease at the main Government maternity hospital in Kingston, Jamaica between 1973 and 1981 detected 311 (149 female) babies with SS disease who were matched by age and gender with 250 (129 female) controls with an AA haemoglobin phenotype. These individuals have been followed from birth with prospective assessment of menarche and detailed documentation of all pregnancies. Results: There were 177 pregnancies in 71 SS patients and 226 pregnancies in 74 AA controls. Mothers with SS disease had more spontaneous abortions (adjusted relative risk [aRR] 3.2, 95% CI 1.6–6.1), fewer live births (aRR 0.7, 95% CI 0.6–0.9) and their offspring were more likely to have a gestational age <37 weeks (aRR 2.1, 95% CI 1.1–3.7) and low birthweight <2.5 kg (aRR 3.0, 95% CI 1.6–5.3). They were more prone to acute chest syndrome (aRR 13.7, 95% CI 4.1–45.5), urinary tract infection (aRR 12.8, 95% CI 1.3–125.9), pre‐eclampsia/eclampsia (aRR 3.1, 95% CI 1.1–8.8), retained placenta (aRR 10.1, 95% CI 1.1–90.3), sepsis (Fisher's Exact test 0.04) and pregnancy‐related deaths (Fisher's Exact test 0.02). Four of five deaths were attributable to acute chest syndrome. There was no genotypic difference in pregnancy‐induced hypertension or postpartum haemorrhage. Conclusion: Pregnancy in SS disease carries risks for both mother and child. The variable characteristics of pregnancy‐related deaths complicate their prevention. Tweetable abstract: Pregnancy in SS disease compared with controls showed increased abortions and stillbirths, fewer live births and maternal deaths in 7% patients. Tweetable abstract: Pregnancy in SS disease compared with controls showed increased abortions and stillbirths, fewer live births and maternal deaths in 7% patients.